Impact of vaping and smoking on maximum respiratory pressures and respiratory function - Mohammad Z. Darabseh; James Selfe; Christopher I. Morse; Hans Degens (International Journal of Adolescence and Youth, 2021)
The effects of electronic-cigarette use (vaping), marketed as a healthier alternative to cigarette smoking (CS), on lung function remain equivocal. Therefore, this study assessed and compared the effects of vaping and CS on maximum respiratory pressures (MRP), respiratory function and carboxyhaemoglobin levels. Forty-four young healthy participants were recruited: vapers (n = 12), cigarette smokers (n = 14), and people who had never vaped nor smoked (control) group (n = 18). Spirometry, MRP and carboxyhaemoglobin levels were measured. Both smokers and vapers had a lower Forced expiratory volume in the first second (FEV1), Peak expiratory flow, FEV1/Forced vital capacity (FEV1/FVC), Forced expiratory flow at 25%, 25–75% of FVC, FEF25-75pred% and higher carboxyhaemoglobin% than controls (p < 0.05). In smokers, but not in vapers, FEV1pred% was lower than in controls (p < 0.01). MRP did not differ significantly between the three groups. Vaping has similar detrimental effects as CS on pulmonary function and may thus not be a healthier alternative to smoking.